L2 learning online: Self-directed learning and gender influence in Indonesian university students - Subekti, Adaninggar Septi (JEES (Journal of English Educators Society), 2022)
The present study was conducted to investigate Indonesian second language (L2) learners’ Self-Directed Learning (SDL) in English during the online classes due to the Covid-19 pandemic and to investigate whether there was a significant difference in SDL between female and male learners. As online learning is implemented nationwide in Indonesia due to the pandemic, it becomes paramount to investigate learners’ SDL, considered very critical in online learning settings where teachers' ability to check learners' progress is not as extensive as it is in the face-to-face mode of instruction. The participants of the study were 187 undergraduate students taking English for Academic Purposes (EAP) classes. Through the data obtained from the online questionnaire, the study found that learners, in general, reported a high level of SDL even though many of them still embraced procrastination behaviours and considered the pragmatic need to pass the EAP class more important than the actual L2 learning. It also found that there was no significant difference between female learners’ SDL and that of male learners. Based on the findings and analysis of the possible factors, possible contributions of the study are presented along with the possible limitations and suggested directions for future research in the field. HIGHLIGHTS: Learners, in general, reported a high level of SDL. Despite that, many of them still embraced procrastination behaviours and considered the pragmatic need to pass the English for Academic Purposes class more important than the actual L2 learning. With the nationwide implementation of online learning in Indonesia due to the pandemic, understanding learners' SDL is crucial